Integration of HIV care into maternal and child health services in the global IeDEA consortium - Humphrey, John; Nagel, Elizabeth; Carlucci, James G.; Edmonds, Andrew; Kinikar, Aarti; Anderson, Kim; Leroy, Valériane; Machado, Daisy; Yin, Dwight E.; Tulio Luque, Marco; Amorissani-Folquet, Madeleine; Mbewe, Safari; et al. (Frontiers in Global Women's Health, 2023)
The WHO recommends the integration of routine HIV services within maternal and child health (MCH) services to reduce the fragmentation of and to promote retention in care for pregnant and postpartum women living with HIV (WWH) and their infants and children exposed to HIV (ICEH). During 2020–2021, we surveyed 202 HIV treatment sites across 40 low- and middle-income countries within the global International epidemiology Databases to Evaluate AIDS (IeDEA) consortium. We determined the proportion of sites providing HIV services integrated within MCH clinics, defined as full [HIV care and antiretroviral treatment (ART) initiation in MCH clinic], partial (HIV care or ART initiation in MCH clinic), or no integration. Among sites serving pregnant WWH, 54% were fully and 21% partially integrated, with the highest proportions of fully integrated sites in Southern Africa (80%) and East Africa (76%) compared to 14%–40% in other regions (i.e., Asia-Pacific; the Caribbean, Central and South America Network for HIV Epidemiology; Central Africa; West Africa). Among sites serving postpartum WWH, 51% were fully and 10% partially integrated, with a similar regional integration pattern to sites serving pregnant WWH. Among sites serving ICEH, 56% were fully and 9% were partially integrated, with the highest proportions of fully integrated sites in East Africa (76%), West Africa (58%) and Southern Africa (54%) compared to ≤33% in the other regions. Integration was heterogenous across IeDEA regions and most prevalent in East and Southern Africa. More research is needed to understand this heterogeneity and the impacts of integration on MCH outcomes globally.